THE MIDDLE EAST - A SPACE OF CONFRONTATION FOR THE INTELLIGENCE SERVICES - Alice-Raimonda COLAN (Annals: Series on Military Sciences, 2025)
The Middle East is one of the most complex and volatile regions of the world, characterized by protracted conflicts, political instability, and a complicated web of alliances and enemies. In this context, intelligence services have become essential players in managing threats, protecting national security and influencing geopolitical dynamics. These agencies are crucial not only for internal security, but also for responding to external challenges, such as terrorism, the proliferation of weapons of mass destruction and cyber threats. This study looks at the role of intelligence services in the Middle East, their structures, their goals and the impact they have on the region and the world.